Dignity In Palliative Care: The Hospice at Skogafoss Falls - Jaskiewicz, John Gerald Jr. (Virginia Tech, 2011)
Hospice is a place of caring, a place where life is measured in quality, not quantity. During a terminally ill patient s final weeks, days or hours, it is important that hospice facilities provide comfort through any and every means possible. The physician administers pain relief, the building has the ability to administer a kind of relief the patient may not even cognitively perceive. Through the eyes of a terminally ill patient, the architect should consider the views, connections and relationships the patient has with their surroundings. Keeping the patients experiences at the forefront of all design decisions, the architect can promote a sense of dignity within the patients that seems to be lost in most modern health care facilities. This thesis proposes a 30-bed hospice to be built along the Skógafoss falls in Skógar, Iceland. The hospice design addresses the patients connections to the physician, structure and natural surroundings through articulation of spaces based on these relationships. The placement of every element within the hospice, from the patients bed to the physicians offices, can have a drastic effect on the patients experiences in many ways. Exploring layouts and forms not common in traditional health care design, the hospice at Skógafoss falls provides an experience unique to any hospice in the world. The spatial connections and materiality of the hospice allow the patients to determine their own relationships to the facility and the natural world beyond. Through simplicity and mindfulness, the hospice can be more than a place to die. Rather it is a place for one to spend their final hours with both comfort and dignity. Master of Architecture